Using Community-Based Truth Commissions to Address Poverty and Related Economic, Social and Cultural Rights Violations: The UK Poverty Truth Commissions as Transformative Justice. (21st February 2022) - Cahill-Ripley, Amanda; Graham, Luke David
Abstract: Following the financial crisis and the imposition of austerity measures within the UK, poverty across the country has widened and deepened. The resulting severe negative impacts on the realization of economic and social rights are still being felt. Accountability of the State for such poverty related human rights violations has predominantly been addressed by judicial or quasi-judicial remedies. However, it is contended that due to limitations of scope and reach, alternative and additional mechanisms encompassing broader forms of justice are required to effectively address poverty and related violations of rights. This article explores the value-added of addressing poverty and related violations of economic, social and cultural rights (ESCRs) using alternative and additional 'justice' mechanisms drawn from the practice of transitional justice, in particular truth and reconciliation commissions (TRCs). Drawing upon the experience of community-based truth and reconciliation commissions, we evaluate the effectiveness of the UK Poverty Truth Commissions (PTCs) as a mechanism for realizing justice for poverty and related human rights violations. The central contention is that while the PTCs constitute an important and meaningful form of transformative justice, there is significant value-added in using a more explicit ESCRs agenda to enhance accountability, recompense and equality and fairness. Overall, the PTCs can help to close the 'justice gap' (Lederach 2001 ) and make a valuable contribution to transformative justice, tackling poverty and realizing ESCRs within the UK.